Natural history of SPINK1 germline mutation related-pancreatitis - Muller, Nelly; Sarantitis, Ioannis; Rouanet, Marie; de Mestier, Louis; Halloran, Christopher; Greenhalf, William; Férec, Claude; Masson, Emmanuelle; Ruszniewski, Philippe; Lévy, Philippe; Neoptolemos, John P.; Buscail, Louis; et al. (EBioMedicine, 2019)
Background - The aim was to describe genetic, clinical and morphological features in a large, multicentre European cohort of patients with SPINK1 related pancreatitis, in comparison with patients with idiopathic pancreatitis (IP). - Methods - All SPINK1 mutation carriers with pancreatic symptoms from two French and one English centers were included. Patients with IP were included in a control group. Genetic, clinical, radiological and biochemical data were collected. - Findings - 209 and 302 patients were included in the SPINK1 and control groups (median follow-up: 8.3 years (3.7-17.4) vs 5.3 (2.5-8.8)). The median age at onset of symptoms was 20.1 years (17.5-22.8) in the SPINK1 group versus 41.2 (35.2-45.2). The age of exocrine pancreatic insufficiency (EPI) onset in the SPINK1 group was 49.5 (44.5-54.6) years vs. 65.2 (62.1-68.3), p < 0.001. SPINK1 patients with EPI were 5.3%, 14.7%, 28.3% and 52.4% at 20, 30, 40 and 50 years. Diabetes occurred 37.7 (33.3-42.1) years following the onset of symptoms in the SPINK1 group vs. 30.6 (17.3-43.8) (p=0.002). SPINK1 patients with diabetes were 7.8%, 13.4%, 26.3% and 43.4% at 30, 40, 50 and 60 years. Seven patients (3.3%) developed pancreatic cancer in the SPINK1 group (versus 3 (0.99%), p=0.1), at a median age of 60 vs 66 years. The cancer risk was 0.8% before 50 years, 11.9%, 27.7%, 51.8% at 60, 70 and 80 years and was 12 times higher than in controls (Cox HR 12.0 (3.0-47.8), p < 0.001). - Interpretation - SPINK1 related pancreatitis is associated with earlier onset and pancreatic insufficiencies. p.N34S SPINK1 may well be associated with cancer.
Gesehen am 09.12.2019